A promising class of luminescent derivatives of Silver(I) and Gold(I)‐N‐heterocyclic carbene. (2nd June 2020) - Jhulki, Lalmohan; Purkait, Rakesh; Kisan, HemantaK.; Bertolasi, Valerio; Isab, AnvarhuseinA.; Sinha, Chittaranjan; Dinda, Joydev
Abstract: Starting from proligand 1‐methyl‐2‐(phenyl)imidazo[1, 5‐a]pyridine‐2‐iumchloride (1 .HCl), 1‐methyl‐2‐(phenyl)imidazo[1, 5‐a]pyridine silver(I)chloride, (2 ) has been prepared. Synthesis, structures and photophysical properties of (2, 2 / −bipyridyl)‐1‐methyl‐2‐(phenyl)imidazo[1, 5‐a]pyridinesilver(I)hexaflurophosphate, (3 ), 1‐methyl‐2‐(phenyl)imidazo[1, 5‐a]pyridinesilver(I)carbazolate, (4 ) and 1‐methyl‐2‐(phenyl)imidazo[1, 5‐a]pyridinegold(I)carbazolate, (5 ) are focused. Herein we have first reported the NHC‐Ag‐(bpy/carbazole). All the complexes have been characterized by elemental analysis, various spectroscopic studies and finally screened for luminescent properties. All the complexes are strongly emissive. Solid state structures of 2, 3, 4 and 5 have been determined by X‐ray diffraction studies. Conventionally, complex 2 adopts linear geometry whereas complex 3 embraces triangular planar geometry around Ag; complex 4 and 5 clinches linear geometry around Ag/Au. All the complexes absorb light within 275–343 nm. Complex 3 is luminous at 407 mn, whereas complex 4 and 5 luminous at 360 nm having short life time 1.00–6.97 ns. The quantum yield (Φem ) of the complexes varies 0.106–0.186. It is expected variation of luminescence arises due to change of metal and the chromophore (bpy/carbazole). Density Functional Theory (DFT) and Temparature Dependent Density Functional Theory (TDDFT) calculations were performed to verify crystallographically derived parameters and to calculate the UV–Vis properties of the ground state as well as of the first excited state of the complexes. Abstract : Synthesis, structures, and luminescent properties of a series of Ag(I)/Au(I) complexes of 1‐methyl‐2‐(phenyl)imidazo[1, 5‐a]pyridine‐2‐ylidene fasten with 2, 2′‐bipyridine or carbazole are described. Electronic and structural data were corroborated with a series of DFT and TDDFT calculations which were in good agreement with experiment.